М. В. Ломоносов о соотношении церковнославянского, древнерусского и “древнего славянского” языков (на материалe eгo записки о А. Л. Шлёцeре) - Успенский, Б. А. (Kalbotyra, 1988)
In the 18th–19th centuries treated discussions on the origin of Church Slavonic took place in Russia. A. Shishkov thinks Church Slavonic to be archaic Russian while N. Karamzin treats Church Slavonic and Old Russian as separate languages belonging to the family of Slavonic languages. It should be noted that it was M. Lomonosov who was the first to oppose clearly and differently Church Slavonic of the 9th century to Old Russian of the 10th–11th centuries. It was done by M. Lomonosov in the review of the plan of Shliotser’s works made by him on July 26th 1764 in the Academy of Sciencies.